2017
DOI: 10.1021/acs.biochem.6b01243
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Na,K-ATPase by Magnesium Ions

Abstract: Since the beginning of investigations of the Na,K-ATPase, it has been well-known that Mg is an essential cofactor for activation of enzymatic ATP hydrolysis without being transported through the cell membrane. Moreover, experimental evidence has been collected through the years that shows that Mg ions have a regulatory effect on ion transport by interacting with the cytoplasmic side of the ion pump. Our experiments allowed us to reveal the underlying mechanism. Mg is able to bind to a site outside the membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 48 publications
0
28
0
4
Order By: Relevance
“…Sodium-potassium adenosine triphosphatase (Na + /K + -ATPase), also known as sodium-potassium pump, is an enzyme that is found in the plasma membrane of almost all animal cells( 32 34 ). Na + /K + -ATPase actively pumps sodium (out of cell) and potassium (into cell) against their concentration gradients to regulate the cell volume, maintain the cell resting potential, enhance cellular transport, affect signal transduction, and control neural activity states( 35 ). It has been shown that Na + /K + -ATPase is expressed in the midpiece of the spermatozoa and has been found to be very important for sperm motility( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sodium-potassium adenosine triphosphatase (Na + /K + -ATPase), also known as sodium-potassium pump, is an enzyme that is found in the plasma membrane of almost all animal cells( 32 34 ). Na + /K + -ATPase actively pumps sodium (out of cell) and potassium (into cell) against their concentration gradients to regulate the cell volume, maintain the cell resting potential, enhance cellular transport, affect signal transduction, and control neural activity states( 35 ). It has been shown that Na + /K + -ATPase is expressed in the midpiece of the spermatozoa and has been found to be very important for sperm motility( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition seen with excess Mg 2+ , likely a result of Mg 2+ binding to a second inhibitory site (Pedemonte & Beaugé, 1983) corroborates the notion of multiple binding sites. Mg 2+ can access the channel connecting the binding sites of the transported ions with the extracellular aqueous phase when the enzyme is in the E 2 conformation, modifying local ion concentrations in the electrolyte, but not affecting pump reaction kinetics (Apell, Hizler, & Schreiber, 2017).…”
Section: The Magnesium Binding Sitesmentioning
confidence: 99%
“…It has been suggested that this ion has a specific binding site in the protein, different from the enzymatic site, and its presence leads to an apparent decrease of the sodium and potassium affinity of binding sites. Magnesium ions reduce binding of sodium ions, which can be caused by both allosteric and electrostatic actions on the Na + ,K + -ATPase [41]. The quantitative estimates made earlier on the basis of competition of sodium and magnesium ions in the cytoplasmic access channel of Na + ,K + -ATPase, showed that the dissociation constant of Na + in the binding site increased by approximately six times in the presence of magnesium ions [27].…”
Section: Resultsmentioning
confidence: 99%
“…The similarity of the effect of both ions species in sign and magnitude is in favor of the electrostatic hypothesis of the magnesium effect on sodium and potassium binding in the E 1 conformation. The presence of Mg 2+ both in the double layer close to the membrane surface and bound to the protein near the entrance to the access channel [41] is expected to create a potential barrier for cations on the way from the solution to the binding sites. Then the decrease of cooperativity can be explained by a rate-limitation of the ion flux from the solution to the binding sites since ions have to jump over the barrier one by one.…”
Section: Resultsmentioning
confidence: 99%